PERENCANAAN PERATURAN ZONASI DI KAWASAN KONSERVASI (STUDI KASUS PECINAN SEMARANG) - Jamilla Kautsary (Jurnal Planologi, 2018)
ABSTRACTZoning regulations for spatial planning in Indonesia are an integral part of the Spatial Detail Plan. The zoning regulation serves as a technical reference for the utilization and control of spatial utilization. This is done to maintain the use of space that develops in accordance with the characteristics of the zone and to minimize negative impacts. Traditional Chinatown settlements have certain characteristics that develop according to historical and spiritual factors of the community. Behind this characteristic is a meaning that is considered very important for this community, so that it cannot be arbitrarily arranged. This paper examines zoning regulations implemented in the Semarang Chinatown area and how far the local characteristics of the zone are used as a consideration of planning zoning regulations for spatial use in the region. This paper uses a rationalistic qualitative deductive approach with empirical description techniques. Some important findings identified from this paper are: first zoning regulations applied in the Spatial Detail Plan are still minimal and limited to the determination of spatial functions, the network system that serves related to the basic coefficient of build, height of the building. Both unique characteristics that must be considered in zoning arrangements in Chinatown such as activity grouping, spatial use rules, especially in skewers zones, and rules of space use around places of worship or sanctified spaces, building height and coefficient of existing buildings have not been considered at all. Recommendations that can be given from this paper are that the minimum zoning regulation components that apply in Indonesia according to the applicable standards are applied with special consideration of the unique characteristics of the region in the spatial arrangement.Keywords:  Zoning, Conservation, Traditional, Chinatown  ABSTRAKPeraturan zonasi dalam penataan ruang di Indonesia merupakan bagian yang tidak terpisahkan dari Rencana Detail Tata Ruang. Peraturan zonasi tersebut berfungsi sebagai rujukan teknis untuk pemanfaatan dan mengendalikan pemanfaatan ruang. Hal ini dilakukan untuk mejaga agar pemanfaatan ruang yang berkembang tetap sesuai dengan karakteristik zona serta untuk meminimalkan dampak negatif. Permukiman tradisional Pecinan memiliki karakteristik tertentu yang berkembang sesuai faktor kesejarahan dan spiritual dari masyarakatnya. Dibalik karakteristik yang ada ini terselip makna yang dianggap sangat penting bagi komunitas ini, sehingga tidak bisa sembarangan untuk diatur. Tulisan ini mengkaji peraturan zonasi yang dilakukan di kawasan Pecinan Semarang dan seberapa jauh karakteristik lokal zona digunakan sebagai pertimbangan perencanaan peraturan zonasi pemanfaatan ruang di kawasan tersebut. Tulisan ini menggunakan pendekatan deduktif kualitatif rasionalistik dengan teknik deskripsi empiris. Beberapa temuan penting yang terindentifikasi dari tulisan ini adalah: pertama peraturan zonasi yang diterapkan dalam Rencana Detail Tata Ruang  masih minim  dan terbatas pada penentuan fungsi ruang, sisten jaringan yang melayani terkait koefisien dasar bangun, ketinggian bangunan. Kedua karakteritik unik  yang harus dipertimbangkan dalam pengaturan zonasi di Pecinan seperti  pengelompokan kegiatan, aturan pemanfaatan ruang khususnya di zona tusuk sate, dan aturan pemanfaatan ruang disekitar tempat peribadatan atau ruang-ruang yang disucikan, keinggian bangunan dan koefisien bangunan eksisting belum di pertimbangkan sama sekali.  Rekomendasi yang bisa diberikan dari tulisan ini adalah minimal komponen peraturan zonasi yang berlaku di Indonesia sesuai standarat yang berlaku diterapkan dengan pertimbangan khusus karakteristik unik kawasan dalam pengaturan ruang.Kata kunci:  Zonasi, Konservasi, Tradisional, Pecinan